2017
DOI: 10.1021/acsomega.7b01054
|View full text |Cite
|
Sign up to set email alerts
|

ecoAO: A Simple System for the Study of Human Aldehyde Oxidases Role in Drug Metabolism

Abstract: Although aldehyde oxidase (AO) is an important hepatic drug-metabolizing enzyme, it remains understudied and is consequently often overlooked in preclinical studies, an oversight that has resulted in the failure of multiple clinical trials. AO’s preclusion to investigation stems from the following: (1) difficulties synthesizing metabolic standards due to the chemospecificity and regiospecificity of the enzyme and (2) significant inherent variability across existing in vitro systems including liver cytosol, S9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…This can be explained if we consider the effect of substrate inhibition. It appears that O6BG does not show any substrate inhibition (Barr et al, 2015), whereas the reported K I value for DACA was 91 mM (Paragas et al, 2017b). We hypothesize that the second substrate molecule would bind to the reduction site and therefore make the reduction happen even more slowly, the same effect we saw by using a reductive substrate 5NQ, and that is why the k 5 value for DACA is lower than that of O6BG.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…This can be explained if we consider the effect of substrate inhibition. It appears that O6BG does not show any substrate inhibition (Barr et al, 2015), whereas the reported K I value for DACA was 91 mM (Paragas et al, 2017b). We hypothesize that the second substrate molecule would bind to the reduction site and therefore make the reduction happen even more slowly, the same effect we saw by using a reductive substrate 5NQ, and that is why the k 5 value for DACA is lower than that of O6BG.…”
Section: Discussionmentioning
confidence: 67%
“…N-(2-dimethylamino)ethyl)acridine-4-carboxamide (DACA) was synthesized as described previously (Paragas et al, 2017b). O 6 -benzylguanine (O6BG) and zaleplon were purchased from Toronto Research Chemicals (North York, ON), zoniporide and dantrolene from Cayman Chemical Company (Ann Arbor, MI), BIBX1382 from Tocris Bioscience (Bristol, UK), and internal standards (phenacetin and 2-methly-4(3H)-quinazolinone), phthalazine, protocatechuic acid, protocatechuate 3,4dioxygenase (Pseudomonas spp.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations